2011
DOI: 10.1021/jf2016286
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Angelica gigas from Different Geographical Origins Using 1H NMR and UPLC-MS Analyses

Abstract: Angelica gigas obtained from different geographical regions was characterized using (1)H nuclear magnetic resonance (NMR) spectroscopy and ultraperformance liquid chromatography-mass spectrometry (UPLC-MS) followed by multivariate data analyses. Principal component analysis (PCA) and orthogonal partial least-squares-discriminant analysis (OPLS-DA) score plots from (1)H NMR and UPLC-MS data sets showed a clear distinction among A. gigas from three different regions in Korea. The major metabolites that contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 45 publications
0
51
0
1
Order By: Relevance
“…We previously showed that primary metabolite profiling enabled us to evaluate the species and cultivation area of Angelica acutiloba (23,24). Recently, primary metabolite profiling contributed to the discrimination of different geographical regions for Salvia miltiorrhiza Bunge (25) and Angelica gigas (26). Primary metabolites, such as sugars and amino acids, could be used as markers to assess species and production area.…”
Section: Evaluation Of the Gc Data By Pcamentioning
confidence: 99%
“…We previously showed that primary metabolite profiling enabled us to evaluate the species and cultivation area of Angelica acutiloba (23,24). Recently, primary metabolite profiling contributed to the discrimination of different geographical regions for Salvia miltiorrhiza Bunge (25) and Angelica gigas (26). Primary metabolites, such as sugars and amino acids, could be used as markers to assess species and production area.…”
Section: Evaluation Of the Gc Data By Pcamentioning
confidence: 99%
“…Environmental factors, such as the site of cultivation, altitude, temperature, sun exposure time, rainfall, climate, and soil can influence the primary and secondary metabolites of plants [20][21][22]. These factors may affect secondary metabolites qualitatively and quantitatively, so their bioactivities could be varied [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These factors may affect secondary metabolites qualitatively and quantitatively, so their bioactivities could be varied [21][22][23]. Therefore, metabolite profiling studies of herbal plants is very important for ensuring their safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not a prediction model is good can be judged in terms of the Q 2 value, and a model is considered to be good if Q 2 > 0.5; if Q 2 > 0.9, a model is considered to have an excellent predictive ability (24). Additionally, permutations test were performed in the PLS-DA model to validate each OPLS-DA model according to validation methods in previous work of A. gigas (17). All Q 2 and R 2 values were higher in the permutation test than in the real model, revealing great predictability and goodness of fit.…”
Section: Orthogonal Projections To Latent Structures-discriminant Anamentioning
confidence: 99%
“…However, the discrimination was performed only by qualitative analysis, and the statistical significance of candidate markers was not mentioned in the reports. One recent report that used statistic analysis for the evaluation of markers by NMR and UPLCeMS is the study on A. gigas from three different regions in Korea (17). The samples analyzed only represented cultivation area as quality factor.…”
mentioning
confidence: 99%